A new approach for mapping forest management areas in Canada - Graham Stinson; Gurp Thandi; Darren Aitkin; Chris Bailey; James Boyd; Michelle Colley; Catherine Fraser; Lane Gelhorn; Kathleen Groenewegen; Adam Hogg; Joe Kapron; Antoine Leboeuf; et al. (The Forestry Chronicle)
Canada’s forests have frequently been characterized using binary classifications such as intact/non-intact or managed/unmanaged. A more nuanced classification approach is needed to better understand the geography of forest management in Canada. The best way to represent Canada’s complex diversity of forest management regimes with a simple classification is to categorize according to ownership, protection status and tenure. We gathered federal, provincial and territorial geospatial datasets and used a binary decision tree approach in GIS to classify land into nine classes: (i) Protected, (ii) Restricted, (iii) Federal Reserve, (iv) Indian Reserve, (v) Treaty/Settlement, (vi) Private, (vii) Long-Term Tenure, (viii) Short-Term Tenure, and (ix) Other. These classes are broad; management intensity may vary considerably within classes. Not all forests in Long-Term Tenure or Short-Term Tenure areas are available for timber supply. Government regulations establish considerable reserve areas within forest management units where harvesting is not permitted. The resulting map dataset is current to 2017 and will need to be updated as land designations change.